Poor farming systems and poverty in Eastern Uganda: Impacts on food security and food safety - Barasa, Daniel (My University, 2023)
This paper is an exploration of the impact of poverty and subsistence farming in Eastern Uganda on food security and food safety. The research draws on existing literature, field-based research, and interviews with local stakeholders to investigate how poor farming systems, characterized by low crop yields, an impoverished soil base, and an emerging environmental crisis, can exacerbate poverty in the region, thereby jeopardizing food security and safety. The literature review reveals that such conditions constrain agricultural productivity, reduce household income, and drive an influx of unhealthy and highly processed foods. Through the field research, preliminary data on farmers’ access to and use of land, credit and extension services is provided, illustrating the extent to which poor farming systems interact with the dynamic of poverty and food insecurity. Interviews with local stakeholders contribute to an understanding of how unequal landholdings, tenure vulnerabilities and shifting climatic conditions curve around and reinforce existing social economic disparities. The paper concludes with policy and recommendations for improving food security and food safety, as well as sustainable development interventions.
Keywords: Farming System; food safety and quality; food security; poverty; Sustainability